Blockade of de novo dNTP biosynthesis pathway delays HIV-1 early life cycle kinetics and dynamics - Mohammad Anwar Siddique; Michael D. McRaven; Muhammad Shoaib Arif; Edward J. Allen; Charia McKee; Shravya Honne; Tahmina Sultana; Baek Kim; Ann M. Carias; João I. Mamede; Thomas J. Hope (mBio)
ABSTRACT The early events of the HIV-1 life cycle, such as reverse transcription, and capsid shedding commonly known as uncoating, are interdependent and tightly regulated, enabling HIV-1 to adapt to diverse host cells. Here, we explored how host cell dNTP pool size modulates the kinetics and dynamics of HIV-1 reverse transcription and uncoating. We optimized an easy-to-use tool to inhibit the ribonucleotide reductase (RNR) catalyzed de novo pathway of dNTP biosynthesis in CHOpgsA-745, HeLa (TZMbl), and owl monkey kidney (OMK) cells. RNR inhibitor rapidly reduced the cellular dNTP pool size, thereby restricting HIV-1 infectivity in a dose-dependent manner. This restriction was reversible upon inhibitor removal, and nucleoside supplementation partially restored infection by enhancing salvage pathways. We find that RNR inhibition slows reverse transcription kinetics and delays the initiation of uncoating in both the capsid integrity and TRIM-CypA restriction assays. Besides, the depletion of intracellular dNTP pools by RNR inhibition leads to significant reductions in both early and late HIV-1 reverse transcription products, with late-stage inhibition comparable to that observed with Nevirapine treatment. To demonstrate the impact of RNR inhibitors on capsid shedding, rather than an off-target effect, we resumed the RNR inhibition-induced delayed initiation of uncoating by reintroducing external dNTPs. This induced recommencement of rapid core integrity loss demonstrating its interplay with the progression of reverse transcription. Therefore, by inhibiting the RNR-catalyzed de novo pathway of dNTP biosynthesis, we have reduced the dNTP pool of the host cells to an extent that delays the kinetics and dynamics of HIV-1 early life events.IMPORTANCECellular dNTP pool homeostasis is maintained by the interplay between the biosynthetic (de novo and salvage) pathways and hydrolyzing networks such as SAMHD1. Inhibiting de novo pathway using RNR inhibitors reduces the host cell dNTP pool size, thereby restricting HIV-1 infectivity reversibly. Whereas the salvage pathways cannot rescue HIV-1 infectivity to the full extent without the de novo pathway. This work correlates HIV-1 infectivity with the dynamic nature of dNTP turnover due to RNR small subunit switching between RRM2 & RRM2B and the action of SAMHD1. The observed modulation of HIV-1 reverse transcription and uncoating in response to RNR inhibition demonstrates the flexibility and adaptability of the virus to replicate in hostile internal cellular environments, which attempt to starve the virus of essential metabolites such as dNTPs. These findings provide insights into how RNR inhibition may impact subsequent steps, such as nuclear localization and integration, offering a foundation for future studies.